Rancang Bangun Tacho Generator Sebagai Sensor Kecepatan Pada Praktikum Kendali Motor-Motor Listrik - Roswaldi Sk; Julsam Julsam (Teknik Elektro Politeknik Negeri Padang, 2009)
The research implementing “Tachogenerator as the sensor for controller of Electric Motor Speed rotation at electric laboratories” Plant (Object controlled) is controlled by the electric motors speed rotation in AC or DC, by setting armature voltage of motor using digital PID controller and fuzzy logic from Personal Computer (PC). Although the load disturbances are changing significantly, but the motor speed rotation can be stabilized by feedback input from tachogenerator which are the focus in this research. PID controller dan fuzzy Logic controller applications are used to find the advantages the disadvatages or controll methode of motor reliability in dinamic controll (speed rotation) which cause the system more stabil. The result can be seen in maintained system responses and the system reliabilty against disturbances.